Lysosome-targeting amplifiers of reactive oxygen species as anticancer prodrugs - Daum, Steffen; Sellner, Leopold (Angewandte Chemie. International edition, 2017)
Cancer cells produce elevated levels of reactive oxygen species, which has been used to design cancer specific prodrugs. Their activation relies on at least a bimolecular process, in which a prodrug reacts with ROS. However, at low micromolar concentrations of the prodrugs and ROS, the activation is usually inefficient. Herein, we propose and validate a potentially general approach for solving this intrinsic problem of ROS-dependent prodrugs. In particular, known prodrug 4-(N-ferrocenyl-N-benzylaminocarbonyloxymethyl)phenylboronic acid pinacol ester was converted into its lysosome-specific analogue. Since lysosomes contain a higher concentration of active ROS than the cytoplasm, activation of the prodrug was facilitated with respect to the parent compound. Moreover, it was found to exhibit high anticancer activity in a variety of cancer cell lines (IC50=3.5-7.2 μm) and in vivo (40 mg kg−1, NK/Ly murine model) but remained weakly toxic towards non-malignant cells (IC50=15-30 μm).